Cuscuta reflexa Roxb. Expedites the Healing Process in Contact Frostbite. (5th October 2020) - Hassan, Waseem; Buabeid, Manal Ali; Kalsoom, Umme; Bakht, Sahar; Akhtar, Imran; Iqbal, Furqan; Arafa, El-Shaimaa A.
Abstract : Frostbite is caused due to extreme vulnerability to cold, resulting in damage of deeper and superficial tissues alike. In this study, we report the anti-inflammatory and wound-healing properties of aqueous methanolic extract of Cuscuta reflexa ( Cs.Cr ) against contact frostbite. Thirty rats were divided into five groups including three treatment groups with increasing doses of Cs.Cr, a standard drug group receiving acetylsalicylic acid (ASA), and a metal bar-induced frostbite group. Frostbite injury was induced by a 3 × 3.5  cm metal bar frozen up to -79°C on shaved skin for continuous 3 minutes. Wounded area percentages were recorded to measure the healing rate in response to Cs.Cr administration. Haematological parameters and malondialdehyde content were also noted. On treatment with Cs.Cr, the healing rate is drastically increased and lipid peroxidation product malondialdehyde was decreased in a dose-dependent manner. Results were compared with frostbite and ASA (standard drug group). These results indicate that Cs.Cr possesses excellent wound-healing properties against frostbite injury and can prove to be a prospective compound in such conditions.